Multiple linear regression equation for chloride estimation of the groundwater for chanthaburi, thailand - Mekparyup J. (2014)
The objective of this study is to estimate Chloride of the groundwater in Chanthaburi, Thailand using multiple regression analysis. The multiple linear regression equation proposed in this study related to Chloride, Total dissolved solids, Iron, Nitrate and Total hardness data which are obtained from the Department of Groundwater Resources, Thailand. Results shows that the best fitted equation to estimate Chloride (y) of the groundwater in Chanthaburi relates to To al dissolved solids (x1) and Total hardness (x4). It can be estimated by \log(y) = 1.22026 + 0.0050531x1 - 0.0019421x4 with adjusted coefficient of determination 0.607 and standard error of estimation 0.717. © 2013 Academic Publications, Ltd.